A Irmandade da Misericórdia de São Paulo e a assistência aos expostos: recolher, salvar e educar (1896-1944) - Silva, Maria Beatriz de Oliveira e (2010)
This research addresses the assistance system of the Irmandade da Misericórdia de São Paulo for exposed children in the late XIX to mid-XX century. The actions and practices of individuals in charge of the system, the power relations, as well as the result of the actions of the ones involved in the exposed children's education were analyzed . The sources' survey was conducted in theArquivo do Museu da Santa Casa de Misericórdia de São Paulo. The Relatórios da Mesa Administrativa for the years 1902 to 1947 were consulted, mainly the ones relative to the years of 1903, 1936, 1943 and 1944. The reports consisted of "reports" sent by the heads of institutions maintained by the Irmandade: Hospital Central, São Luiz Gonzaga, Externato São José, Hospital dos Lázaros, Asilo Santo Antonio and the Asilo dos Expostos. The exposed children's stewardshipreports were composed of two parts. In the first part, the steward reported the major events and the development of the activities taking place in the various sections of the asylum: leadership, school, wet nurses. The second part, written by the physician in charge for the children's medical assistance, discoursed on the of health, hygiene and wet nurses' nurture conditions . Those reports allow to identify the actions and practices of the stewards. From 1943 on, the kindergarten teacher's report was also available, as well as the social worker's one. A literature search was also conducted about São Paulo city's socioeconomic background and also on childhood social history, with an emphasis on the institutionalized child. It was possible to observe that Misericordia's assistance was dynamic, that is, it incorporated, although slowly, innovations concerning assistance and education to poor children. However, interventions in order to provide social mobility to those children were not detected, but rather an acceptance with their social status